G347(P) Accuracy of information giving following a child's first seizure by specialist and non-specialist paediatricians in epilepsy: Is there variation in practice?. (27th April 2016) - Motaleb, F; Rittey, C
Abstract : Aim: NICE recommends that children following a first non-febrile seizure be seen by a specialist, defined as a Paediatrician with training and expertise in epilepsy, as soon as possible. Yet there is evidence (Epilepsy 12 Audit) to show that many patients are being acutely assessed and managed by non-specialist Paediatricians. This then raises questions as to whether these patients and families are receiving the same level of clinical care as those who see a specialist? Method: Eighty-two Paediatricians across Yorkshire and the Humber completed an online questionnaire assessing their practice in regards to information giving to parents following their child's first generalised tonic-clonic seizure (GTCS). Non-specialist cohorts included fifteen Paediatric Specialist ST4-ST5, eighteen Paediatric Specialist ST6-ST8 and thirty-one Paediatric Consultants without epilepsy interest. Specialist cohorts included eight Paediatric Consultants and one Associate Specialist with epilepsy interest and nine Paediatric Neurologists. Results: 75% of doctors provided recognised (Epilepsy Action UK) first aid advice for GTCS management (55/75) and bathroom safety (56/72). However approximately 73% of doctors (55/75) inappropriately advised a parent to automatically call an ambulance if their child were to have a further GTCS. In addition large variation in advice given was identified across and between non-specialist and specialist cohorts. This included sixty-eight doctors providing forty-one different pieces of seizure safety advice. In addition 47% of doctors (31/66) provided nine dissimilar instructions on the use of further rescue medication following a failure of seizure cessation after one dose. This included advice such as "No more Midazolam to be given" to "Give second dose after 10 min". In addition one Neurologist advised "Give second dose after 20 min" which was not in keeping with any other Neurologists or non-specialists. Education in epilepsy (e.g. Paediatric Epilepsy Training Level 1–3) did appear to benefit non-specialists but not on a consistent basis. Doctors did self identify that previous Neurology experience was important in giving them confidence to provide this information. Conclusion: Approach to information giving following a child's first seizure is not consistent amongst and between non-specialists and specialists in epilepsy. However education in epilepsy management as well as previous Neurology experience was associated with a positive impact.